2002
DOI: 10.1152/ajprenal.00176.2001
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonic induction of SGK1 and Na+transport in A6 cells

Abstract: Serum and glucocorticoid-regulated kinase-1 (SGK1) is a serine-threonine kinase that is regulated at the transcriptional level by numerous regulatory inputs, including mineralocorticoids, glucocorticoids, follicle-stimulating hormone, and osmotic stress. In the distal nephron, SGK1 is induced by aldosterone and regulates epithelial Na+ channel-mediated transepithelial Na+ transport. In other tissues, including liver and shark rectal gland, SGK1 is regulated by hypertonic stress and is thought to modulate epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 55 publications
6
52
0
Order By: Relevance
“…Nuclear TonEBP is increased throughout the medulla in dehydrated versus water-loaded animals (26). It is noteworthy that Rozansky et al showed that sgk1, in addition to being stimulated by increases in extracellular tonicity, is also stimulated by decreases in extracellular tonicity (47). The latter has been demonstrated using hypo-osmotic induction of A6 cells and confirmed here using rat IMCD cells.…”
Section: Figuresupporting
confidence: 82%
“…Nuclear TonEBP is increased throughout the medulla in dehydrated versus water-loaded animals (26). It is noteworthy that Rozansky et al showed that sgk1, in addition to being stimulated by increases in extracellular tonicity, is also stimulated by decreases in extracellular tonicity (47). The latter has been demonstrated using hypo-osmotic induction of A6 cells and confirmed here using rat IMCD cells.…”
Section: Figuresupporting
confidence: 82%
“…The different molecularweight bands of Sgk1 have been attributed exclusively to aberrant migration, owing to phosphorylation of residues T253 and S422 upon activation of Sgk1 by insulin or other agonists (Park et al, 1999;Rozansky et al, 2002). We demonstrate that additional bands of lower molecular weight than Sgk1 correspond to different translational isoforms.…”
Section: Mechanism That Produces the Sgk1 Isoformsmentioning
confidence: 74%
“…This regulation also involves serum-and glucocorticoid-kinase (SGK1) that prevents ENaC degradation and mitogen-activated protein kinase (MAPK) that in contrast stimulates channel degradation (31,32). In A6 cells, hypotonicity, as well as aldosterone, induces SGK1 expression (7). However, studies in the SGK1 knockout mouse demonstrated that renal salt handling is normal when the animals are on a standard salt intake but impaired with dietary salt restriction, suggesting that SGK1 participates in, but does not fully account for, mineralocorticoid regulation of sodium reabsorption (33).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hormonal stimulation (aldosterone, vasopressin, insulin), other factors are known to increase epithelial sodium transport, including hypotonic and mechanical stimulation (7). In recent work, Jans et al (8) have shown that hypotonic treatment of renal epithelia induces a transient increase in intracellular Ca 2ϩ through a mechanism that is sensitive to the purinergic P2 receptor antagonist suramin applied to the basolateral border only.…”
mentioning
confidence: 99%